Strengthening Substantive Representation of Women through the Engagement Model of the Women’s Movement with the DPR and DPRD in Indonesia - Atnike Nova Sigiro (Yayasan Jurnal Perempuan, 2019)
Although it has not yet reached an ideal composition, the adoption of a 30% quota of women in elections in Indonesia has increased the number of women in parliament, both at the central level (House of Representative/DPR) and at the regional level (Regional House of Representatives/DPRD). However, the issue of women’s representation in parliament is not only a matter of representation based on sex, but also of substantive representation, where women’s political agenda can be voiced. One of the concepts developed by feminist thinking is the concept of critical actors. This article seeks to explain how women’s organizations and parliamentarians are critical actors that encourage women’s involvement with parliament. This article explains how the involvement between women’s organizations and parliament can strengthen the substantive representation of women in both the DPR and the DPRD. The article is developed based on studies on engagement models of MAMPU’s partners with the DPR and DPRD.